A Novel Technique for Repositioning of a Migrated ILUVIEN® (Fluocinolone Acetonide) Implant into the Anterior Chamber. Issue 2 (December 2015) - El-Ghrably, Ibraheem; Saad, Ahmed; Dinah, Christiana
Abstract Introduction Fluocinolone acetonide (FAc) intravitreal implant (ILUVIEN® ; Alimera Sciences Limited, Aldershot, UK) has been approved in the UK for the treatment of chronic diabetic macula edema, insufficiently responsive to available therapies. It is inserted into the vitreous cavity through a 25-gauge needle. Migration of the implant to the anterior chamber (AC) can occur through gaps in the posterior capsule especially in vitrectomized eyes. Early removal of AC-dislocated FAc implant is essential to prevent corneal edema and damage from raised intraocular pressure. Aim To demonstrate a simple and novel technique, with a previous capsular tear, for removal of AC-migrated FAc implant and reinsertion into the vitreous cavity without compromising implant integrity. Method A side port incision was created with a keratome and an anterior chamber maintainer introduced and secured. Subsequently, a corneal incision was created at 12 o'clock through which a 23-gauge backflush needle (flute needle) was advanced into the anterior chamber and passive suction used to secure the implant. The flute needle was then placed through the defect in the posterior capsule and the exit port blocked, causing loss of suction and allowing the implant to fall into the posterior segment. The sulcus intraocular lens (IOL) was centralized simply by manipulating it approximately 180 degrees to provide adequate anterior capsule support. Results The FAc implant was successfully removed from AC in two patients and reinserted into the vitreous cavity without damage or complications either for the eye or the implant. IOL in both patients were repositioned to close the gap in posterior capsule. After 2 months, the implant remains in the vitreous cavity. This paper presents data from one of these cases. Conclusion Using 23-gauge flute needle to retrieve dislocated FAc implant is a safe and easy technique. Funding Alimera Sciences Ltd.